Impact of tibial baseplate malposition on kinematics, contact forces and ligament tensions in TKA: A numerical analysis. (March 2020) - Fottner, Andreas; Woiczinski, Matthias; Schröder, Christian; Schmidutz, Florian; Weber, Patrick; Müller, Peter E.; Jansson, Volkmar; Steinbrück, Arnd
Abstract: Purpose: Malposition of implant components in total knee arthroplasty (TKA) has consequences on tibiofemoral kinematics, contact forces and ligament tensions. To evaluate the impact of tibial baseplate malpositioning in the same knee, we conducted a computer simulation. Methods: An established weight-bearing finite element model of a fixed bearing TKA was used for the computer simulation. To evaluate the influence of tibial baseplate malposition, calculations were consecutively performed in neutral position, at 3° and 6° of internal and external rotation and at 3 mm and 6 mm of medial and lateral translation. Results: The highest effect of malposition was observed for ligament tensions, with a tendency of a greater influence for the 6 mm translation compared to 6° of rotation. Changes in contact forces and tibiofemoral kinematics were according to the alterations of ligament tensions. The highest ligament tension, contact force and femoral roll-back were registered for 6 mm medialization of the tibial baseplate. Discussion: Tibial baseplate malposition effects ligament tensions, tibiofemoral contact forces and kinematics and has a risk of unfavorable clinical results due to postoperative pain, reduced range of motion, instability and a higher rate of early loosening. Therefore, surgeons should aim for a neutral position of the tibial baseplate. Graphical abstract: Image 1 Highlights: Biomechanical differences of total knee arthroplasty with tibial baseplate malposition. Finite element methods to determine kinematics, contact forces and ligament tensions. Tibial position highly alters tension of posterior cruciate and collateral ligaments. Tibial baseplate malposition affects inlay stresses and knee kinematics.